Nigeria : business opportunities - Metra Consulting Group; Tewson, Geoffrey; Cotton, David (London : The Group, 1977)
This report sets out in digestible form the strategy of development outlined in the third National Development plan. It furthers goes on to examine the business opportunities which should arise from the plan as it involves in practice and also the existing situation sector by sector.
Includes bibliographical references
hza 01/02/2019
Loans
Keywords: Investments, Foreign; Nigeria